CRISPR/Cas-edited iPSCs and mesenchymal stem cells: a concise review of their potential in thalassemia therapy - Shu, Jiaojiao; Xie, Xin; Wang, Sixi; Du, Zuochen; Huang, Pei; Chen, Yan; He, Zhixu (Frontiers in Cell and Developmental Biology, 2025)
Thalassemia, a prevalent single-gene inherited disorder, relies on hematopoietic stem cell or bone marrow transplantation as its definitive treatment. However, the scarcity of suitable donors and the severe complications from anemia and iron overload pose significant challenges. An immediate need exists for a therapeutic method that addresses both the illness and its associated complications. Advancements in stem cell technology and gene-editing methods, such as clustered regularly interspaced short palindromic repeats along with its associated protein (CRISPR/Cas), offer encouraging prospects for a therapy that could liberate patients from the need for ongoing blood transfusions and iron chelation treatments. The potential of genetic reprogramming using induced pluripotent stem cells (iPSCs) to address thalassemia is highly promising. Furthermore, mesenchymal stem cells (MSCs), recognized for their capacity to self-renew and differentiate into multiple lineages that include bone, cartilage, adipose tissue, and liver, demonstrate potential in alleviating several complications faced by thalassemia patients, including osteoporosis, cirrhosis, heart conditions, respiratory issues, and immune-related disorders. In this review, we synthesize and summarize relevant studies to assess the therapeutic potential and predict the curative effects of these cellular approaches.